Integrated Work Breakdown Structure for Shipbuilding on Department Group Machinery Part Zone Block Engine Room - Wolfgang Busse; M. Badrus Zaman; Pratama Akbar (International Journal of Marine Engineering Innovation and Research, 2021)
In the work breakdown structure for shipbuilding of machinery outfitting is related to machinery, ducting, hvac & piping, steel work, and insulation. Integrated work breakdown structure is one of the shipbuilding methods involving in management, so that design time is shorter. The ducting, HVAC & piping is the system based on the contract assignment and drawing approval by classification society. Then, we compare the effect of each Time Estimation. Then, continue with combine product and project structure. Problem start with how do we compare old with new WBS technology, no optimization process, and no working breakdown structure for the outfitting in the engine room. Bar chart, combination of industrial and financial system with design software also program project evaluation and review technique methodology will be used. Results obtained a work breakdown structure for Guidelines. The Aim was for optimization process time. The schedule created compared with the actual schedule that occurs so that we can see there is a difference of time shows that the shipyard applies integration. This also will lead to man-hour optimization. It is concluded that an integrated work breakdown structure can be applied to obtain the shipyard design in a shorter time.